2010
DOI: 10.1021/ja1072614
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Highly Regioselective Oxidation of C−C Triple Bonds without Acid Additives: Propargyl Moieties as Masked α,β-Unsaturated Carbonyls

Abstract: Gold-catalyzed intermolecular oxidations of internal alkynes have been achieved with high regioselectivities using 8-alkylqinoline N-oxides as oxidants and in the absence of acid additives. Synthetically versatile α,β-unsaturated carbonyls are obtained in good to excellent yields and with excellent E-selectivities. A range of functional groups such as THP, MOMO, N 3 , OTBS, and NBoc are tolerated. This reaction allows to mask α,β-unsaturated carbonyls as propargyl moieties, thus offering a practical solution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(127 citation statements)
references
References 40 publications
6
120
0
1
Order By: Relevance
“…According to a method reported by Lu et al, the gold-promoted oxidation of alkyne 212 using 2-bromopyridine N-oxide gave the enone 214. 31 Finally, diastereoselective epoxidation of enone 214 to deliver a mixture (5:1) of epoxides (-)-citrinadin A 216 and …”
Section: Wood Et Al's Enantioselective Total Synthesis Of (+)-Citrinamentioning
confidence: 99%
“…According to a method reported by Lu et al, the gold-promoted oxidation of alkyne 212 using 2-bromopyridine N-oxide gave the enone 214. 31 Finally, diastereoselective epoxidation of enone 214 to deliver a mixture (5:1) of epoxides (-)-citrinadin A 216 and …”
Section: Wood Et Al's Enantioselective Total Synthesis Of (+)-Citrinamentioning
confidence: 99%
“…Early in 2010 our research group showed for the first time [8] that reactive a-oxo gold carbenes [9] could be readily accessed by simple intermolecular oxidation [10] of terminal alkynes, [11] therefore allowing substitution of toxic a-diazo ketones with benign and readily available alkynes (Scheme 1). This approach was later applied to the preparation of oxetan-3-ones from easily available propargyl alcohols.…”
mentioning
confidence: 99%
“…[20] To our delight, this new cationic gold(I) complex offered a significant improvement (Table 1, entry 12). Inspired by our recent work that did not use acid additives, [11] the reaction was attempted without MsOH. Pleasingly, azetidin-3-one 2 was formed in an 85 % (82 % isolated) yield, and the reaction rate did not decrease to a significant extent (Table 1, With the optimal reaction conditions secured, the reaction scope was then studied.…”
mentioning
confidence: 99%
“…4,7,28,[51][52][53][54][55][56][57][58] In particular, the gold-catalyzed oxygen transfer of a nucleophilic oxygen atom to an alkyne group is synthetically useful. [59][60][61][62][63][64][65] To further explore the reactivity of Au catalysts towards oxygen-atom transfer reactions, we investigated the gold-catalyzed addition of O-nucleophiles to alkynes to produce synthetically important vinyl ether products in excellent yields and regioselectivities at room temperature. Although these vinyl ethers are generally not stable enough to be isolated with standard silica gel chromatography, they were stable in our hands.…”
Section: Functionalization Of Alkynes Through Addition Of Nhydroxy Hementioning
confidence: 99%
“…[59][60][61][62][63][64][65][178][179][180] In 2009, Asensio and co-workers applied the oxygen transfer concept in their intermolecular gold-catalyzed sulfoxide addition to alkynes that allowed the preparation of sulfur containing arenes (Scheme 16b).…”
Section: 50mentioning
confidence: 99%